2018
DOI: 10.20491/isarder.2018.561
|View full text |Cite
|
Sign up to set email alerts
|

Devam Bağlılığı, Presenteeism ve İşten Ayrılma Niyeti Arasındaki İlişki: Beş Yıldızlı Otel İşletmelerinde Bir Araştırma - The Relationship Between Continuance Commitment, Presenteeism and Turnover Intention: A Research on Five Star Hotel Enterprises

Abstract: Bu çalışmanın temel amacı, otel işletmelerindeki çalışanlarda devam bağlılığı, presenteeism ve işten ayrılma niyeti arasındaki ilişkiyi ortaya koymaktır. Araştırmada uygulanan yöntem betimsel araştırma yöntemidir. Araştırmanın örneklemini 2017 yılı Mayıs-Temmuz ayları arasında Antalya bölgesindeki sekiz adet beş yıldızlı otel işletmesindeki 407 çalışan oluşturmaktadır. Araştırmada veri toplama yöntemi olarak anket tekniği kullanılmıştır. Anket formu dört bölümden oluşmaktadır. Birinci bölümünde demografik deği… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…In addition to causing a loss of productivity in employees, presenteeism also creates increased costs for medical and psychological treatments. Therefore, the negative consequences of this situation can seriously harm individuals, society, and businesses (Hemp, 2004;Kendir et al, 2018). One study identified various personal factors of employees related to presenteeism, such as health and work attitudes.…”
Section: The Relationship Between Presenteeism and Job Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to causing a loss of productivity in employees, presenteeism also creates increased costs for medical and psychological treatments. Therefore, the negative consequences of this situation can seriously harm individuals, society, and businesses (Hemp, 2004;Kendir et al, 2018). One study identified various personal factors of employees related to presenteeism, such as health and work attitudes.…”
Section: The Relationship Between Presenteeism and Job Stressmentioning
confidence: 99%
“…In the context of a highly competitive global landscape, organizations are compelled to enhance the performance and efficiency of their workforce in order to effectively attain their objectives. The significance of employee well-being in relation to corporate performance is particularly highlighted in studies focusing on human resources (Baker-McClearn et al, 2010;Bierla et al, 2013;Kendir et al, 2018). Conversely, it appears implausible for employees to consistently maintain good health.…”
Section: Introductionmentioning
confidence: 99%
“…There is ample evidence of the various elements of employee wellbeing (e.g. emotional exhaustion, level of embeddedness) and actual turnover (Huyghebaert et al , 2019); however, limited evidence exists for presenteeism and ETIs (Kendir et al , 2018). The ETI is mainly shown to have adverse effects on organisational productivity as employees' feelings or desire to resign may lead to lower productivity and presenteeism.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…Örneğin içsel analizini yaparak yenilik geliştirme yoluna gidilirse işletmenin hangi alanda yeniliğe ihtiyaç duyulduğu bilinir. Dışsal analiz yapmak ise rakiplerin hangi yönde güçlü olduklarını bilmek açısından önemlidir (Kendir, Arslan, & Özçelik Bozkurt, 2018).…”
Section: II Yenilik Performansı Kavramıunclassified